The spectral test of the Boolean function linearity - Porwik, Piotr (Zielona Góra: Uniwersytet Zielonogórski)
The paper discusses the problem of recognizing the Boolean function linearity. A spectral method of the analysis of Boolean functions using the Walsh transform is described. Linearity and nonlinearity play important roles in the design of digital circuits.
Keywords: Walsh coefficients; coefficients distribution; Boolean functions; bent functions; linearity measure of a Boolean